Integrated analysis of rumen metabolomics and metataxonomics to understand changes in metabolic and microbial community in Korean native goats under heat stress - Eom, Jun Sik; Choi, Youyoung; Lee, Shin Ja; Kim, Hyun Sang; Jo, Seong Uk; Bae, Dongryeoul; Lim, Dong-Hyun; Kim, Eun Tae; Kim, Sang Bum; Lee, Sung Sill (Scientific reports, 2024)
Heat stress (HS) is an impactful condition in ruminants that negatively affects their physiological and rumen microbial composition. However, a fundamental understanding of metabolomic and metataxonomic mechanisms in goats under HS conditions is lacking. Here, we analyzed the rumen metabolomics, metataxonomics, and serum metabolomics of goats ( n = 10, body weight: 41.08 ± 1.83 kg) under optimum temperature period (OTP) (HS-free, temperature humidity index (THI): 57.13 ± 3.98) and high temperature period (HTP) (HS-exposed, THI: 80.27 ± 1.22) conditions, to identify changes in key metabolites and the rumen microbiome induced by HS. Compared to the OTP and HTP conditions, metabolomic analysis revealed significant changes in rumen metabolites related to energy and amino acid metabolism, with HTP goats showing potential rumen metabolic biomarkers, such as butyrate, isopropanol, phenylacetate, and 2-oxoisocaproate ( P < 0.001). Serum analysis revealed significant changes in energy metabolism and immune response, with HTP goats showing potential metabolic biomarkers, including acetate, betaine, glucuronate, and kynurenine ( P < 0.05). Metataxonomic analysis revealed that HS affected the alpha diversity measurements, including the Chao1 estimate ( P < 0.05) and evenness ( P < 0.05) between OTP and HTP groups. Through the metabolic association of the rumen microbiome with the metabolome, we found that Fibrobacter and Ruminococcus were enriched in HTP and positively correlated with ruminal microbial metabolites, such as acetate. In addition, Prevotellaceae UCG-003, which was denoted as the keynote genus in the HTP, co-occurred with acetate-producing bacteria such as Quinella and Ruminococcus . Furthermore, we identified that Oscillospiraceae UCG-002, an enriched bacterial genus in HTP, showed a positive correlation with functional features, such as biotin and sulfur metabolism. Our study provided fundamental insights into how HS affected the physiology and rumen microbial compositions of goats and how both microbiome and host-dependent mechanisms contributed to these changes. These findings could potentially suggest strategies for mitigating the adverse effects of HS, including changes in the microbial population and energy metabolism in goats.